Direct sampling method for identifying magnetic inhomogeneities in limited-aperture inverse scattering problem. (15th December 2020) - Ahn, Chi Young; Ha, Taeyoung; Park, Won-Kwang
Abstract: The direct sampling method (DSM) in limited-aperture inverse scattering problems for transverse electric (TE) polarization is considered. Based on the asymptotic expansion formula in the presence of small targets, we demonstrate that the indicator function of DSM can be represented by an infinite series of Bessel functions of integer order and correspondingly examine various properties of DSM. Simulation results with noisy data are created to support theoretical results. Based on the identified structure of the indicator function, we design a new indicator function of DSM, analyze its mathematical structure, and generate simulation results to demonstrate its effectiveness and improvement.